Assessing feasibility of polyarylate-clay nanocomposites towards improvement of gas selectivity - Bhole, Yogesh S.; Wanjale, Santosh D.; Kharul, Ulhas K.; Jog, Jyoti Prakash (Journal of Membrane Science, 2007)
Polymer-clay nanocomposites are well known to reduce the penetrant permeability by following tortuous path. Effects of such reduction in gas permeability on variation in selectivity of nanocomposites prepared using a high permeability polymer were examined. The polyarylate: poly (tetramethyl bisphenolA-iso/terephthalate) that exhibits high permeability and moderate selectivity was chosen for making nanocomposites with two organically modified clays (Cloisite 6A and 10A) by solution intercalation method. The nanocomposite formation for various clay loadings (3, 5 and 7% w/w) in polyarylate was ascertained by change in physical properties (X-ray diffraction, DMA, TEM). Behavior of solution viscosity and nanocomposite density indicated existence of polymer-clay layer interactions. As anticipated, though the gas permeability of pure gases, viz., He, N-2, CH4 and CO2 exhibited decrease, it was not monotonous. This decrease was more for larger gases (N-2, CH4 and CO2) in comparison to the decrease for smaller gas (He) permeability. This led to a decrease in CO2/N-2 and CO2/CH4 selectivities and increase in He/CO2 selectivity; while He/CH4 selectivity was increased substantially at 7% clay loading. This variation indicated feasibility of nanocomposites formation as a tool for improving selectivity of certain gas pairs. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Gas permeation; Nanocomposites; polyarylates; selectivity; solution intercalation

Effect of substituent polarity, bulk, and substitution site toward enhancing gas permeation in dibromohexafluorobisphenol-A based polyarylates - Ishole, Yogesh S.; Karadkar, Prasad R.; Kharul, Ulhas K. (Journal of Polymer Science Part B-Polymer Physics, 2007)
The gas permeation properties of polyarylates were tuned by varying nature and site of substituents present on both of its monomers, viz., bisphenol and dicarboxylic acid. The phenyl rings of hexafluorobisphenol-A were substituted in asymmetric manner by polar bromine to obtain dibromohexafluorobisphenol-A. This bisphenol was polymerized with equimolar mixture of iso- and terephthalic acid (base case), bromo- and nitroterephthalic acid (polar group substituted acids), 4,4'-hexafluoroisopropylidene bis(benzoic acid), and t-butyl isophthalic acid (bulky group containing acids). Physical properties and gas permeation properties of these polyarylates were investigated to assess combined effects of asymmetric nature of bisphenol substitution, polar nature of substituent bromine, hexafluoroisopropylidene group present at the bridge position of bisphenol, and substituent present on the acid moiety. The combination of these substituent types led these polyarylates to lie near Robeson upper bound. The gas sorption analysis and estimation of diffusivity in these polyarylates shed a light on observed variations in gas permeation properties by attempted structural variations. (c) 2007 Wiley Periodicals, Inc.
Keywords: asymmetric substitution; Diffusion; Gas permeation; gas sorption; polyarylates; selectivity; structure-property relations

Gas sorption and transport in polyarylates: effect of substituent symmetry and polarity - Karadkar, Prasad B.; Kharul, Ulhas K.; Bhole, Yogesh S.; Badhe, Yogesh P.; Tambe, Sanjeev S.; Kulkarni, Bhaskar D. (Journal of Membrane Science, 2007)
The gas sorption properties of polyarylates based on bisphenol-A possessing symmetric/asymmetric substitution by nonpolar -CH3 group and symmetrically linked terephthalic acid were examined. The effects of substitution of polar bromine on terephalic acid moiety of polyarylate based on asymmetrically substituted bisphenol were also studied for physical, sorption and transport properties. The estimation of dual mode sorption parameters, solubility and diffusion coefficient revealed that nature of the substituent and substitution type plays a crucial role in depicting permeation properties. An asymmetric substitution by -CH3 group increased solubility coefficient of pure gases (N-2, O-2, CH4 and CO2) up to 27% and symmetric substitution increased the same up to 106%. This was coupled with 7-35% increase in solubility selectivity in both cases of substitution, which ascertained the usefulness of methyl group substitution in polyarylates based on terephalic acid. The pressure dependency of solubility coefficients and solubility selectivity was also investigated for these polyarylates. The sorption and transport properties of these polyarylates correlated well with physical properties of polyarylates and gases studied. The sorption/desorption kinetics of symmetrically substituted TMBisA-T was performed in order to deduce time dependent sorption behavior and to evaluate diffusivity coefficient. The apparent diffusion coefficients from sorption kinetics, desorption kinetics and from steady-states permeation-sorption were compared. The diffusion coefficients of CH4 and N-2 deduced by these methods correlated well with each other. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Diffusion; kinetics; permeation; polyarylates; Sorption

Polyarylate based thin film composite (TFC) membranes: effects of coating parameters, gutter layer, and intrinsic material properties - Chendake, Yogesh J.; Bhole, Yogesh S.; Lohokare, Harshada R.; Kharul, Ulhas K. (Separation Science and Technology, 2010)
Investigations in thin film composite (TFC) membrane formation with polyacrylonitrile ultrafiltration membrane as a support and three polyarylates with sequentially increased polarity are reported. Effects of TFC membrane preparation parameters viz., concentration of the coating solution, dip time, presence of solvent in pores of UF membrane support, and presence of the gutter layer were examined towards the formation of the selective skin layer, which was assessed by gas permeation analysis. TFC membranes prepared using dimethyl bisphenol-A based polyarylate exhibited similar to 3 orders of magnitude higher permeability and comparable selectivity as that of its dense membrane.
Keywords: Gas permeation; gutter layer; polarity; polyarylates; TFC membrane